Hanging centimeter-scale monolayer graphene and method of making the same
Patent Information
- Application Number
- CN202510492104.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2026-10-23
AI Technical Summary
然而,现有的转移方法无法有效消除样品在制备过程中所积累的各类宏观应力,难以获得稳定的厘米级悬空单层石墨烯,所制备的石墨烯会很快(约1小时内)破裂
[0021]本发明中,通过在特定的激光切割参数设计下,对石墨烯的至少部分边界进行精确的激光切割处理,有效释放了其在制备过程中积累的各类宏观应力,尤其是张应力,从而避免了应力集中引发的裂纹扩展或膜层破裂现象。该方法显著提升了石墨烯的结构稳定性,最终获得了长时间稳定且悬空的厘米级单层石墨烯,为其在光电器件、纳米传感器等高性能器件中的应用提供了材料基础。
Smart Images

Figure CN122957828A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of graphene technology, and particularly to a method for preparing suspended centimeter-scale monolayer graphene and the suspended centimeter-scale monolayer graphene. Background Technology
[0002] Centimeter-scale monolayer graphene has attracted widespread attention and research from the scientific community due to its high crystallinity, extremely high in-plane mechanical strength, excellent out-of-plane flexibility, extremely high electrical and thermal conductivity, high light transmittance, atomic-level thickness (approximately 0.4 nanometers), atomic-level ion-barrier effect, and commercial availability, and has shown very broad application prospects.
[0003] Currently, commercially produced large-area (e.g., centimeter-scale) graphene is mainly grown on metal substrates such as copper using chemical vapor deposition (CVD). For applications, it typically needs to be transferred to the target material. Common graphene transfer methods include wet and dry methods, with wet methods being the most prevalent. However, existing transfer methods cannot effectively eliminate the various macroscopic stresses accumulated during sample preparation, making it difficult to obtain stable centimeter-scale suspended monolayer graphene. The prepared graphene tends to break down quickly (within approximately one hour).
[0004] In summary, there are still many challenges in preparing stable and suspended centimeter-scale monolayer graphene. Summary of the Invention
[0005] In view of this, the main objective of the present invention is to provide a method for preparing suspended centimeter-scale monolayer graphene. The method provided by the present invention, by laser-cutting at least a portion of the boundaries of the graphene, can produce long-term stable centimeter-scale monolayer graphene with most of its boundaries (e.g., more than 50% of its perimeter) suspended. A further objective of the present invention is to provide suspended centimeter-scale monolayer graphene obtained by this method.
[0006] To achieve the above objectives, the present invention provides the following technical solution.
[0007] The first aspect of the present invention provides a method for preparing suspended centimeter-scale monolayer graphene, comprising at least the following operations:
[0008] S1, a solid transfer agent layer is formed on one side surface of the graphene containing the substrate at the centimeter scale, resulting in a first stack with a layer structure of substrate-graphene-solid transfer agent layer;
[0009] S2, process the first stack to remove the substrate, and obtain a second stack with a layer structure of graphene-solid transfer agent layer;
[0010] S3, the second stack is heated to remove the solid transfer agent layer, yielding the graphene layer; and
[0011] S4, a laser beam is used to cut at least a portion of the boundary of the graphene layer to obtain a suspended centimeter-scale monolayer graphene; wherein the power p of the laser beam is 5W to 15W, the cutting rate v is 0.2cm / s to 0.7cm / s, and wherein the power p and the cutting rate v satisfy 100V. 2 +0.216p 2 -6.6v×p-20v-1.5p+7.9<0, and the laser beam spot diameter is less than 0.1mm.
[0012] In some embodiments, operation S1 includes applying a solid transfer agent to one side surface of the graphene by vapor deposition or solution coating to form a solid transfer agent layer with a thickness of 30 μm to 50 μm.
[0013] In some embodiments, the solid transfer agent is selected from paraffin, camphor, aluminum chloride, and sulfur, with camphor being preferred.
[0014] In some embodiments, prior to operation S2, the preparation method further includes fixing the first stack between two fixing plates with centimeter-sized holes in the center.
[0015] In some implementations, fixation is performed using a heat-release adhesive.
[0016] In some embodiments, operation S3 includes: performing a first heat treatment on the second stack to remove the heat-release adhesive; and then performing a second heat treatment to remove the solid transfer agent.
[0017] In some embodiments, the second stack is subjected to a first heat treatment at 70°C to 100°C and a second heat treatment at 60°C to 100°C.
[0018] In some embodiments, operation S4 includes: after the solid transfer agent layer is removed, moving the laser beam to the boundary of the graphene layer at a speed of less than 1 cm / s, and then cutting off at least a portion of the boundary of the graphene layer; and in operation S4, isolating the processing environment of the graphene layer from the surrounding environment while eliminating static electricity near the graphene layer.
[0019] In some embodiments, the substrate is a metal substrate, such as a Cu substrate; optionally, in operation S2, the substrate is removed by etching, for example, by an aqueous solution of a saturated solid transfer agent containing 0.8 mol / L to 1.5 mol / L ferric chloride.
[0020] A second aspect of the present invention provides a suspended centimeter-scale monolayer graphene, optionally prepared by the preparation method described in the first aspect, wherein the area of the optionally suspended centimeter-scale monolayer graphene is 0.9 cm². 2 ~1.5cm 2 .
[0021] In this invention, by precisely laser-cutting at least a portion of the boundaries of graphene under specific laser cutting parameters, various macroscopic stresses accumulated during the preparation process, especially tensile stress, are effectively released, thereby avoiding crack propagation or film rupture caused by stress concentration. This method significantly improves the structural stability of graphene, ultimately obtaining long-term stable and suspended centimeter-scale monolayer graphene, providing a material basis for its application in high-performance devices such as optoelectronic devices and nanosensors. Attached Figure Description
[0022] Figure 1 This is a flowchart illustrating the preparation process of suspended monolayer graphene according to one embodiment of the present invention.
[0023] Figure 2 These are photographs of the suspended single-layer graphene during the preparation process in Example 1 of this invention.
[0024] Figure 3 This is a photograph of the suspended single-layer graphene in Example 1 of this invention after 365 days of preservation.
[0025] Figure 4 This is a graph obtained by fitting the process parameters of the laser cutting process in the embodiments and comparative examples of this invention using Mathematica software. Detailed Implementation
[0026] The following detailed description discusses exemplary embodiments. The specific embodiments included herein should not be construed as limiting the invention. Furthermore, while specific language may be used to describe features, actions, and / or structures in the embodiments described herein, the claims are not limited to the described features, actions, and / or structures. Those skilled in the art will understand that other embodiments, including improvements, are within the spirit and scope of the invention.
[0027] Throughout this specification, unless otherwise specified, the terminology used herein should be understood as having the meaning as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0028] It should be noted that, in the embodiments of the present invention, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a method or apparatus that includes a list of elements includes not only the elements expressly stated, but also other elements not expressly listed, or elements inherent to implementing the method or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other related elements in the method or apparatus that includes that element.
[0029] The first aspect of this invention provides a method for preparing suspended centimeter-scale monolayer graphene, comprising at least the following operations:
[0030] S1, a solid transfer agent layer is formed on one side surface of the graphene containing the substrate at the centimeter scale, resulting in a first stack with a layer structure of substrate-graphene-solid transfer agent layer;
[0031] S2, process the first stack to remove the substrate, and obtain a second stack with a layer structure of graphene-solid transfer agent layer;
[0032] S3, the second stack is heated to remove the solid transfer agent layer and obtain the graphene layer;
[0033] S4, a laser beam is used to cut at least a portion of the boundary of the graphene layer to obtain a suspended centimeter-scale monolayer graphene; wherein the power p of the laser beam is 5W to 15W, the cutting rate v is 0.2cm / s to 0.7cm / s, and wherein the power p and the cutting rate v satisfy 100V. 2 +0.216p 2 -6.6v×p-20v-1.5p+7.9<0; and the laser beam spot diameter is less than 0.1mm.
[0034] It should be understood that the term "suspended centimeter-scale monolayer graphene" refers to a single-atom-thick layer of graphene composed of carbon atoms arranged in splines. 2 Two-dimensional carbon materials with hybrid orbitals forming a hexagonal honeycomb lattice have an area on the order of centimeters and are in a suspended state without contact with any substrate.
[0035] It should be understood that the term "boundary" refers to the boundary portion in a two-dimensional carbon material, which may include serrated boundaries, armchair-shaped boundaries, mixed boundaries, or irregular boundaries, etc. The graphene sheet material of this application is particularly polygonal in shape, such as quadrilaterals, rectangles, or squares. Of course, the graphene sheet material can also be circular, in which case it has only one continuous boundary. The term "at least partial boundary" means at least 50% of the perimeter of the two-dimensional graphene material involved, such as at least 60%, 70%, 75%, or 80%. For example, when the graphene layer is quadrilateral in shape, the at least partial boundary can be three of the four boundaries.
[0036] It should be understood that in the above-described laser beam cutting operation, the plane containing the graphene (two-dimensional carbon material) is considered as a coordinate system constructed using the common X and Y axes. The cutting direction is along the circumferential direction of the graphene layer, and the cutting width is 1 / 10 to 1 / 3 of the length of the object being cut (i.e., graphene) perpendicular to the cutting direction (or the diameter when it is circular), such as 1 / 10, 1 / 8, 1 / 7, 1 / 6, 1 / 5, 1 / 4, or 1 / 3. For example, for a 1.5cm * 1.5cm square graphene material, the cutting can be performed along three sides. On two of the parallel sides, the cutting width is 0.25cm, and on the other side, the cutting width is 0.5cm, thus obtaining a final 1.0cm * 1.0cm square graphene material. However, this is not the only possibility, and those skilled in the art can set different cutting widths according to their final needs.
[0037] It should be understood that the term "laser beam cutting" refers to an advanced processing technology that uses a high-energy laser beam to cut materials. The laser beam is the energy source for laser cutting and possesses characteristics such as high monochromaticity, high directionality, and high brightness. In laser cutting, the laser beam is typically generated by a laser, and its wavelength, power, and spot size have a significant impact on the cutting effect. This application does not specifically limit the laser wavelength, as long as the graphene has a high absorption rate of the laser, thus achieving effective cutting.
[0038] The term "power" refers to the energy output of a laser per unit time, usually measured in watts (W) or kilowatts (kW). Power reflects the energy intensity of the laser beam and is one of the key indicators for measuring laser cutting capability. Within the laser power range defined in this application, effective cutting of graphene can be achieved while avoiding significant heating of the surrounding air, thereby reducing damage to the graphene due to airflow disturbance.
[0039] The term "cutting rate" refers to the speed at which the laser beam moves across the material. The cutting speed directly affects cutting efficiency and quality. Excessive speed may result in incomplete cutting and exacerbate air turbulence during the movement; conversely, insufficient speed increases the heat-affected zone, generates significant air turbulence, and reduces cutting quality. The cutting rate range described in this application balances both cutting efficiency and cutting quality.
[0040] The term "spot diameter" refers to the diameter of the focused laser beam. Within the range of spot diameters defined in this application, the energy density of the laser beam is maintained within a corresponding range, thereby producing excellent cutting accuracy and maintaining high energy utilization.
[0041] In this invention, the boundaries of graphene are precisely laser-cut under specific laser cutting conditions, particularly with specific power, cutting rate, and spot diameter. During the graphene fabrication process, graphene accumulates macroscopic stress, which severely affects its structural stability and can easily lead to crack propagation or film rupture. High-precision laser cutting can effectively release the macroscopic stress borne by the graphene, alleviate structural tension, improve structural stability, and ultimately obtain long-term stable, suspended centimeter-scale monolayer graphene.
[0042] In some embodiments, graphene containing a substrate can be obtained by depositing graphene on a substrate using methods well known in the art, such as chemical vapor deposition.
[0043] In some embodiments, the substrate is a material known in the art for use as a graphene substrate, which can be a metal substrate, such as a gold substrate, a Cu substrate, a Ni substrate, etc., or a non-metal substrate, such as a silicon dioxide substrate, etc.
[0044] In some embodiments, to obtain a relatively flat graphene surface, the metal substrate needs to be electrochemically polished before chemical vapor deposition of graphene. In one specific embodiment, the Cu substrate is electrochemically polished to make its surface smooth and flat, facilitating the deposition of flat graphene with a low defect concentration.
[0045] In some implementations, the metal substrate / graphene obtained by chemical vapor deposition (CVD) needs to be planarized before forming the solid transfer agent layer. This is because although the graphene obtained by CVD along with the metal substrate is relatively flat, wrinkles can form on the metal substrate when it is removed from the growth furnace and during possible trimming. To reduce the stress exerted on the graphene by these wrinkles, the metal substrate / graphene can be placed on the surface of a layer of polyethylene terephthalate (PET), and then covered with another layer of PET, forming a sandwich structure with the metal substrate / graphene in the middle. The PET / metal substrate / graphene / PET composite layer is then rolled using a glass rod or other rod-shaped instrument to reduce wrinkles on the metal substrate.
[0046] In some embodiments, operation S1 includes: placing a centimeter-sized graphene containing a substrate in a sealed container, and applying a solid transfer agent to one side surface of the graphene by vapor deposition to form a solid transfer agent layer with a thickness of 30 μm to 50 μm. Controlling the thickness of the solid transfer agent layer within this range allows it to provide stable support for the graphene during operation S2 and also enables rapid removal during operation S3. Exemplarily, the thickness of the solid transfer agent layer is a value within a range of 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, or any combination thereof.
[0047] In some embodiments, the solid transfer agent is selected from paraffin, camphor, aluminum chloride, and sulfur. In one specific embodiment, the solid transfer agent is camphor.
[0048] In some embodiments, operation S1 includes performing a vapor deposition process at 70°C to 100°C to apply a solid transfer agent to one side surface of the graphene. Exemplarily, the vapor deposition temperature is a value between 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, or any combination thereof.
[0049] In some embodiments, operation S1 includes coating a solid transfer agent solution onto one side surface of the graphene containing the substrate, and heating the graphene coated with the solid transfer agent solution at a temperature of 70°C to 130°C, thereby forming a solid transfer agent layer on the graphene surface. Exemplarily, heating is performed at values within the range of 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, or any combination thereof.
[0050] In some embodiments, the solvent for the solid transfer agent solution is one or more of chlorobenzene, toluene, and acetone.
[0051] In some embodiments, the mass concentration of the solid transfer agent solution is 60% to 80%. The mass concentration of the solid transfer agent solution refers to the ratio of the mass of the solid transfer agent to the volume of the solvent. If the mass concentration of the solid transfer agent solution is too low, it becomes difficult to form a solid transfer agent layer on the graphene surface. Exemplarily, the mass concentration of the solid transfer agent solution is a value within a range of 60%, 65%, 70%, 75%, 80%, or any combination thereof.
[0052] In some embodiments, prior to operation S2, the preparation method further includes fixing the first stack between two fixing plates with centimeter-sized holes in the center.
[0053] In some implementations, fixation is performed using a heat-release adhesive.
[0054] It should be understood that the term "heat-release adhesive" refers to an adhesive that has good adhesion at room temperature and can firmly bond two object surfaces, but its adhesion will significantly decrease or even disappear after being heated to a specific temperature, thus making it easy to separate the bonded objects.
[0055] In some embodiments, during operation S2, the substrate is removed by etching, for example, using a ferric chloride solution. Specifically, the etching process involves immersing the first stack in a saturated solid transfer agent aqueous solution containing ferric chloride at a concentration of 0.8 mol / L to 1.5 mol / L, preferably a saturated camphor aqueous solution containing ferric chloride at a concentration of 1.2 mol / L. Using the saturated solid transfer agent aqueous solution containing ferric chloride as the etching solution allows for the etching removal of the metallic Cu substrate without dissolving the solid transfer agent. Exemplarily, the concentration of ferric chloride in the saturated solid transfer agent aqueous solution is a value within the range of 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, or any combination thereof. It should be understood that when the solid transfer agent is insoluble in water, "saturated solid transfer agent aqueous solution" refers to the solvent water.
[0056] In some embodiments, operation S3 includes: performing a first heat treatment on the second stack to remove the heat-release adhesive; and then performing a second heat treatment to remove the solid transfer agent.
[0057] In some embodiments, the second laminate is subjected to a first heat treatment at 70°C to 100°C, and a second heat treatment at 60°C to 100°C. Exemplarily, the temperature of the first heat treatment is a value within a range of 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, or any combination thereof. Exemplarily, the temperature of the second heat treatment is a value within a range of 60°C, 70°C, 80°C, 90°C, 100°C, or any combination thereof.
[0058] Performing the first heat treatment at the above temperature allows the solid transfer agent to sublimate rapidly, removing the solid transfer agent layer without the need for solvents. Furthermore, there is no solid transfer agent residue on the graphene surface, and no other impurities are introduced.
[0059] In some embodiments, operation S4 includes: after the solid transfer agent layer is removed, moving the laser beam to the boundary of the graphene layer at a speed of less than 1 cm / s, and then cutting off at least a portion of the boundary of the graphene layer; and in operation S4, isolating the processing environment of the graphene layer from the surrounding environment, while eliminating static electricity near the graphene layer, thereby reducing graphene breakage caused by airflow disturbance and electrostatic force.
[0060] In some implementations, during operation S4, the workbench is isolated from the surrounding environment by a baffle, and common static electricity removal methods (such as grounding discharge or using an antistatic brush) are used to eliminate static electricity near the graphene layer, thereby reducing airflow disturbance and graphene breakage caused by electrostatic forces.
[0061] In some implementations, when the graphene layer is quadrilateral, a laser beam is used to cut three boundaries of the material, leaving only one boundary for suspension; when the graphene layer is pentagonal, a laser beam is used to cut four boundaries of the material, leaving only one boundary for suspension; when the graphene layer is circular, a laser beam is used to cut most of the boundaries of the material, leaving only at least a portion of the boundaries for suspension.
[0062] The present invention also provides a suspended centimeter-scale monolayer graphene, which is prepared by the preparation method of the present invention.
[0063] In some implementations, the suspended centimeter-scale monolayer graphene has an area of 0.9 cm². 2 ~1.5cm 2 For example, the area of the suspended monolayer graphene is 0.9 cm². 2 1.0cm 2 1.1cm 2 1.2cm 2 1.3cm 2 1.4cm 2 1.5cm 2Or the value between any two of them within a range.
[0064] Example
[0065] The present invention will be described in more detail below through embodiments. It should be understood that the embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the art or in accordance with the product manual.
[0066] Example 1
[0067] The fabrication process of suspended centimeter-scale monolayer graphene is shown in the schematic diagram. Figure 1 and actual photos Figure 2 As shown:
[0068] Step S1: Cut out a 1.5×1.5cm piece. 2 The copper-based graphene was cleaned to remove impurities from the back of the copper substrate, then fixed onto a silicon wafer and placed in the mouth of a glass bottle containing camphor. The glass bottle was then heated on a heating stage at 160°C for 20 minutes, thereby depositing a 40μm thick camphor layer on the surface of the graphene, resulting in the first stack with a layer structure of copper-graphene-camphor.
[0069] Step S2: Remove the first stacked layer from the silicon wafer and then clamp it in the center at a depth of 1.3 × 1.3 cm. 2 The copper substrate is placed between two heat-release adhesive sheets with square holes, and then vertically immersed in a saturated camphor aqueous solution containing 1.2 mol / L ferric chloride (i.e., etching solution) for etching. After the copper substrate is completely etched, the etching solution is released, and a saturated camphor aqueous solution is introduced for cleaning until the liquid becomes colorless and transparent. Then the liquid is drained, and the second stack of graphene-camphor layer is taken out.
[0070] Step S3: Transfer the second stack to a horizontal position with a 1×1cm center. 2 On the square-hole evaporation platform, the camphor side is facing upwards. The evaporation platform is then heated to 70°C to remove the heat-release adhesive. The temperature is then maintained until the camphor is completely evaporated. During the heating process, a baffle can be used to isolate the evaporation platform from the surrounding environment to reduce airflow disturbance, thus obtaining a graphene layer.
[0071] Step S4: After the camphor has completely evaporated, slowly move the laser beam (wavelength 445nm) at a speed of 0.5cm / s to... Figure 1At the graphene layer boundary ① shown, the three boundaries of the graphene layer were sequentially cut along ①-②-③ under the conditions of power p of 5W, cutting speed v of 0.2cm / s, and spot diameter of 0.06mm. The cutting width at ① and ③ was 0.25cm, and the cutting width at ② was 0.5cm, resulting in a graphene layer with an area of 1cm². 2 Furthermore, it consists of a single layer of graphene suspended on three sides. During the graphene cutting process, a baffle separates the operating table from the surrounding environment, while an anti-static brush is used to eliminate static electricity near the graphene layer, thereby reducing airflow disturbance and electrostatic forces.
[0072] Subsequently, the obtained monolayer graphene was examined using an optical microscope to check for any damage.
[0073] Subsequently, the monolayer graphene prepared in Example 1 was placed in a metal box and stored at room temperature and pressure for 365 days. The results showed no cracking when examined by an optical microscope, indicating that the suspended centimeter-sized graphene prepared in this application has good stability.
[0074] Example 2
[0075] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under the conditions of a power of 5W and a cutting rate of 0.3cm / s.
[0076] Example 3
[0077] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under the conditions of 8W power and a cutting rate of 0.2cm / s.
[0078] Example 4
[0079] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under the conditions of 8W power and a cutting rate of 0.3cm / s.
[0080] Example 5
[0081] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under conditions of 8W power and a cutting rate of 0.5cm / s.
[0082] Example 6
[0083] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under conditions of 12W power and a cutting rate of 0.3cm / s.
[0084] Example 7
[0085] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under conditions of 12W power and a cutting rate of 0.5cm / s.
[0086] Example 8
[0087] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under conditions of 12W power and a cutting rate of 0.7cm / s.
[0088] Example 9
[0089] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under conditions of 15W power and a cutting rate of 0.5cm / s.
[0090] Example 10
[0091] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under conditions of 15W power and a cutting rate of 0.7cm / s.
[0092] Comparative Example 1
[0093] Suspended monolayer graphene was prepared using the same method as in Example 1, except that step S4 was omitted and the monolayer graphene prepared in step S3 was used as the final product.
[0094] Comparative Example 2
[0095] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under the conditions of a power of 2W and a cutting rate of 0.2cm / s.
[0096] Comparative Example 3
[0097] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under the conditions of a power of 5W and a cutting rate of 0.7cm / s.
[0098] Comparative Example 4
[0099] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under the conditions of 8W power and a cutting rate of 0.7cm / s.
[0100] Comparative Example 5
[0101] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under conditions of 12W power and a cutting rate of 0.2cm / s.
[0102] Comparative Example 6
[0103] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under conditions of 15W power and a cutting rate of 0.3cm / s.
[0104] Comparative Example 7
[0105] Suspended monolayer graphene was prepared using the same method as in Example 1, except that in step S4, the three boundaries of the graphene layer were sequentially cut off under conditions of 15W power and a cutting rate of 0.8cm / s.
[0106] The preparation process parameters of the suspended centimeter-scale monolayer graphene in the above embodiments and comparative examples are shown in Table 1, and the performance test results of the suspended centimeter-scale monolayer graphene are shown in Table 2.
[0107] Table 1. Preparation process parameters of monolayer graphene in Examples 1 to 10 and Comparative Examples 1 to 7
[0108] project Laser power (W) Laser cutting rate (cm / s) Example 1 5 0.2 Example 2 5 0.3 Example 3 8 0.2 Example 4 8 0.3 Example 5 8 0.5 Example 6 12 0.3 Example 7 12 0.5 Example 8 12 0.7 Example 9 15 0.5 Example 10 15 0.7 Comparative Example 1 - - Comparative Example 2 2 0.2 Comparative Example 3 5 0.7 Comparative Example 4 8 0.7 Comparative Example 5 12 0.2 Comparative Example 6 15 0.3 Comparative Example 7 15 0.8
[0109] Table 2 shows the structural integrity test results of monolayer graphene in Examples 1 to 10 and Comparative Examples 1 to 7.
[0110]
[0111]
[0112] The results above show that by controlling the laser beam power and cutting rate within the range described in this study, stable and suspended centimeter-scale monolayer graphene can be prepared. This is because the laser locally heats the air, causing airflow disturbance, and the movement of the laser head also causes airflow disturbance, both of which can lead to graphene breakage. Therefore, it is necessary to control the laser beam power and cutting rate within the optimized range described in this study.
[0113] like Figure 4As shown, the power p is controlled within the range of 5W to 15W, and the cutting speed v is controlled within the range of 0.2cm / s to 0.7cm / s, and the power p and the cutting speed v satisfy 100V. 2 +0.216p 2 When -6.6v×p-20v-1.5p+7.9<0, centimeter-scale monolayer graphene with three sides suspended and long-term stable performance can be prepared.
[0114] Although the invention has been described with reference to specific exemplary embodiments thereof, many different variations, modifications, etc., will become apparent to those skilled in the art. Through a study of the disclosure and the appended claims, those skilled in the art can understand and implement variations of the disclosed embodiments in practicing the invention.
Claims
1. A method for preparing suspended centimeter-scale monolayer graphene, comprising at least the following operations: S1, a solid transfer agent layer is formed on one side surface of the graphene containing the substrate at the centimeter scale, resulting in a first stack with a layer structure of substrate-graphene-solid transfer agent layer; S2, process the first stacked layer to remove the substrate, and obtain a second stacked layer with a layer structure of graphene-solid transfer agent layer; S3, the second stack is subjected to heat treatment to remove the solid transfer agent layer, yielding a graphene layer; and S4, using a laser beam to cut at least a portion of the boundary of the graphene layer to obtain the suspended centimeter-scale monolayer graphene; wherein the power p of the laser beam is 5W to 15W, the cutting rate v is 0.2cm / s to 0.7cm / s, and wherein the power p and the cutting rate v satisfy 100V. 2 +0.216p 2 -6.6v×p-20v-1.5p+7.9<0; and the spot diameter of the laser beam is less than 0.1mm.
2. The preparation method according to claim 1, wherein, Operation S1 includes: applying the solid transfer agent to one side surface of the graphene by vapor deposition or solution coating to form a solid transfer agent layer with a thickness of 30 μm to 50 μm.
3. The preparation method according to claim 1 or 2, wherein, The solid transfer agent is selected from paraffin, camphor, aluminum chloride, and sulfur, with camphor being preferred.
4. The preparation method according to any one of claims 1 to 3, wherein, Before operation S2, the preparation method further includes fixing the first stack between two fixing plates with centimeter-sized holes in the center.
5. The preparation method according to claim 4, wherein, The fixation is achieved using a heat-release adhesive.
6. The preparation method according to claim 5, wherein, Operation S3 includes: performing a first heat treatment on the second stack to remove the heat-release adhesive; and then performing a second heat treatment to remove the solid transfer agent.
7. The preparation method according to claim 6, wherein, The second stack is subjected to the first heat treatment at 70°C to 100°C, and the second heat treatment is subjected to 60°C to 100°C.
8. The preparation method according to any one of claims 1 to 7, wherein, Operation S4 includes: after the solid transfer agent layer is removed, moving the laser beam to the boundary of the graphene layer at a speed of less than 1 cm / s, and then cutting off at least a portion of the boundary of the graphene layer; and in operation S4, isolating the processing environment of the graphene layer from the surrounding environment, while eliminating static electricity near the graphene layer.
9. The preparation method according to any one of claims 1 to 8, wherein, The substrate is a metal substrate, such as a Cu substrate; optionally, in operation S2, the substrate is removed by etching, for example, by an aqueous solution of a saturated solid transfer agent containing 0.8 mol / L to 1.5 mol / L ferric chloride.
10. A suspended centimeter-scale monolayer graphene, optionally prepared by the preparation method according to any one of claims 1 to 9, wherein the area of the suspended centimeter-scale monolayer graphene is optionally 0.9 cm². 2 ~1.5cm 2 .
